Factors Affecting the Integration of Pediatric TB Screening in Kabale District of Uganda: A Cross Sectional Study - Mandera I; Ayebazibwe G; Tumusiime A; Byamukama T; Mfitumukiza V; Tamu Munezero JB; Nduhukire T; Maniple EB (Dove Medical Press, 2024)
Immaculate Mandera,1 Geoffrey Ayebazibwe,2 Alex Tumusiime,1 Topher Byamukama,3 Valence Mfitumukiza,1 John Bosco Tamu Munezero,1 Timothy Nduhukire,4 Everd B Maniple3 1Department of Nursing Sciences, Kabale University, Kampala, Uganda; 2Department of Pharmacology, Kabale University, Kampala, Uganda; 3Department of Community Health, Kabale University, Kampala, Uganda; 4Department of Pediatrics and Child health, Kabale University, Kampala, UgandaCorrespondence: Immaculate Mandera, Email imandera@kab.ac.ugBackground: Globally, > 1.1 million children had tuberculosis (TB) and > 214,000 died in 2022. The integration of pediatric TB screening should help in the identification and management of cases among children attending clinics at entry points. This study aimed to establish the extent of integrating pediatric TB screening into mainstream childcare activities and the factors affecting integration of TB screening among children.Methods: A cross-sectional design using both quantitative and qualitative methods. Simple random sampling was used to select and observe 40 participants for integration of TB screening in the routine assessment of children. Twenty key informants were interviewed and two focus group discussions conducted on the integration of pediatric TB screening.Results: Of the 302 children assessed, only 41.1% underwent pediatric TB screening integrated in their assessment. A binary logistic regression model using Wald chi-square showed that a cadre having worked at outpatient department (OPD) and young child clinic (YCC) significantly affected integration, with a p-value of 0.002 and 95% CI (1.040- 1.152) and a p-value of 0.002 and 95% CI (1.000- 1.519). Participants who had 3 to 5 years in service were 7.05 times more likely to integrate pediatric TB screening at the OPD and Cadres who had over 6 years in service were 6.32 times more likely at the YCC. Being a nurse or a midwife was associated with an increased likelihood of integrating pediatric tuberculosis screening. Knowledge, skills, and confidence gaps in screening and assessing for tuberculosis in children among staff and lack of necessary logistics were identified barriers.Conclusion: The integration of pediatric TB screening in routine assessments at the OPD/YCC was low. Focus more on HC IIIs to improve health workers' involvement and capacity to integrate TB screening at entry points in health facilities and provide logistics.Keywords: Pediatric, tuberculosis, integration and screening